In-silico evaluation of putative maternal semiochemicals of pigs with receptor proteins - Sankarganesh, Devaraj; Balasundaram, Ambritha; Sampath, Hayavadhan; Manjunath, Diya; Doss C., George Priya (Frontiers in Molecular Biosciences, 2025)
Piglets at weaning experience stress owing to environmental changes. Mixing unfamiliar littermates also induces fighting and biting behaviors among them, affecting their welfare. In addition, post-weaning weight gain or loss is also influenced during the first week of weaning. Many compounds have been identified in the secretions of sows to address these behavioral and welfare issues; nevertheless, the positive influence of these compounds on piglet behavior and welfare is not fully understood. Therefore, we sought to study the interaction between the compounds (myristic acid, oleic acid, lauric acid, palmitic acid, 3-methyl phenol, tiglic aldehyde, and skatole, reported as maternal pheromones/urinary metabolites) and receptor proteins using computational approaches. We used five proteins, including alpha-1-acid glycoprotein (AGP), odorant binding protein (OBP), salivary lipocalin (SAL), pheromaxein, and Von Ebner’s Gland Protein (VEGP). We utilized molecular docking with AutoDock Vina and molecular dynamics simulations (MDS) using GROMACS to examine the stability of interactions between the listed compounds and proteins. The binding energies for the docked complexes ranged between −3.4 and −6.7 kcal/mol. Through analysis of the lowest root mean square deviation (RMSD) and hydrogen bond formations, we identified that at least one of the fatty acids exhibited optimal docking with four distinct proteins. The RMSD data for these complexes also indicated stability over a 100-ns MDS period. However, the post-MDS Molecular Mechanics/Poisson Boltzmann Surface Area (MM/PBSA) binding energy data revealed that palmitic acid had the highest stabilizing energy across all five proteins compared to other complexes. Additionally, myristic acid and oleic acid also exhibited a high binding affinity with the proteins. Taken together, our findings suggest that fatty acids could be the most effective semiochemicals for managing behavioral and welfare issues in weaning piglets.